Case report: Whole exome sequencing identifies a novel variant in the HPRT1 gene in a male with developmental delay - Zheng, Haoyang; Chen, Gui; Wang, Tingting; Cheng, Weisheng; Yuan, Jing; Liu, Fang; Xu, Yuanhong (Frontiers in Genetics, 2025)
Lesch-Nyhan syndrome (LNS, OMIM #300322) is a rare X-linked genetic disorder caused by variants in the HPRT1 gene, which codes for the Hypoxanthine-guanine phosphoribosyltransferase (HGPRT). HPRT1 gene variants disrupt normal purine metabolism, leading to the involvement of multiple organ systems, primarily characterized by hyperuricemia, dystonia, and neurological abnormalities, which makes LNS clinically heterogeneous and diagnostically challenging. Here, we report a rare case of a 27-year-old Chinese male exhibiting severe lower limb motor disorders, hyperuricemia, and intellectual development delay. Blood tests showed hyperuricemia and whole exome sequencing (WES) identified a novel hemizygous variant in the HPRT1 (NM-000194.3) gene: c.104T > C in exon 2, respectively. Bioinformatics techniques indicated that the variant may disrupt the activity of HGPRT. According to the clinical presentation, diagnostic examination, and WES results, the patient was finally diagnosed with LNS. This study identified a previously unreported pathogenic variant in the HPRT1 gene. Although no curative therapy is currently available for HPRT1 gene variants at present, a definite diagnosis of its genetic etiology is of great significance for genetic counseling and family planning.